The impact of COVID-19 pandemic on home spatial design / Lim Su Ching and Muhammad Faizal Abdul Rani - Lim, Su Ching; Abdul Rani, Muhammad Faizal (Universiti Teknologi MARA, Perak, 2023)
This literature review is aimed to identify the impact on home spatial design during the covid-19 pandemic. The covid-19 pandemic and the need to put people into lockdown, quarantine, and self-isolation at home require a reflection on the quality and capacity of home spatial to adjust to a specific function for they are not designed. The adjustment is to ensure the health and well-being of people during the pandemic and predict the future home spatial design for more human-centric. The qualitative method was conducted by viewing 50 papers and articles related to the pandemic, working from home, spatial design, residential real estate, habitability, and resilience from March 2020 to Dec 2021. The review indicates that the Covid-19 pandemic do influence the spatial design from the government enforcement of lockdown, fear of meeting people, and the "stay at home" lifestyle aspect. The pandemic increases people's need to control their living space, safe space, and the use of home space. This review will not only be useful to safeguard people's physical and mental health but with respect to the deficiencies and preferences of users about their homes. It can be taken as a starting point for updating the Malaysia development plans. In addition, it benefits real estate developers as a lifestyle reference on the design of healthy residential buildings in the future.